2014
DOI: 10.1186/1472-684x-13-26
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy near the end of life: a retrospective single-centre analysis of patients’ charts

Abstract: BackgroundChemotherapy near the end of life is an issue frequently discussed nowadays. The concern is that chemotherapy could cause more harm than good in a palliative situation; this is even truer as the patient nears death. The objective of our study is to evaluate the aggressiveness of patient care near the end of life by determining how many cancer patients receive chemotherapy during their final weeks.MethodsIn a retrospective analysis of patient charts, we investigated whether cancer patients had been tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 12 publications
4
47
3
Order By: Relevance
“…In accordance with what we found, a prospective study has revealed that patients receiving palliative chemotherapy were more likely to die in an intensive care unit rather than at home, compared with those not receiving this treatment . Through comparison, we found the median age of our cohort was relatively younger than what others have reported . In our study, patients younger than 56 years underwent more aggressive EOL chemotherapy but presented significantly better survival.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with what we found, a prospective study has revealed that patients receiving palliative chemotherapy were more likely to die in an intensive care unit rather than at home, compared with those not receiving this treatment . Through comparison, we found the median age of our cohort was relatively younger than what others have reported . In our study, patients younger than 56 years underwent more aggressive EOL chemotherapy but presented significantly better survival.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, 116 (24.3 %) patients who died from advanced cancer received chemotherapy in the last month of life. Percentage is in line with literature data [1,[3][4][5][6][7]. It is commonly acknowledged that age, performance status, tumor sensitivity, survival prognosis, and comorbidities should be considered in every [4].…”
Section: Discussionmentioning
confidence: 65%
“…Signs of deterioration and side effects should be monitored closely to avoid overtreatment. The incidence of chemotherapy in the last month of life of patients with advanced cancer varies between 11.7 and 37 % [1,[3][4][5][6][7]. The reasons for this overtreatment are many.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have consistently shown that patients who receive end‐of‐life chemotherapy are younger . Older patients are more likely to value quality of life over life prolonging measures as compared to younger patients .…”
Section: Discussionmentioning
confidence: 99%